Portuguese vaulting systems at the dawn of the early modern period: Between tradition and innovation - Genin, S.; De Jonge, K.; Palacios Gonzalo, J. C. (Proceedings of the Third International Congress on Construction History, 2009)
The Portuguese hall churches of the so-called Manueline Period (end of the fifteenth and beginning of the sixteenth century) are generally seen as straddling two contradictory stylistic phenomena. While their formal repertory announces the Renaissance, their conception and execution follow the geometrical and technical principles used by the gothic builders. Nave and aisles are unified spatially, a common goal in all Europe at the time. In the transversal section unification of the vaults is achieved through a continuous curved profile from side wall to side wall. In Portuguese historiography this is seen as characteristic of João de Castilho with the so-called ‘barrel vault’ of the Hieronymite church at Belém as his masterpiece. The attribution is a polemic issue, but nonetheless relevant. Our investigation has indeed revealed additional examples that certainly deserve a global presentation considering the pertinence of the author issue and of its broader European context.